Functional Communication Training: The Strength of Evidence Across Disabilities. (October 2018) - Gerow, Stephanie; Davis, Tonya; Radhakrishnan, Supriya; Gregori, Emily; Rivera, Gabby
Functional communication training (FCT) is a commonly used, often recommended intervention that involves teaching a functionally equivalent communicative response to replace challenging behavior. The purpose of this literature review was to evaluate the strength of the evidence for the use of FCT. A systematic review of the literature resulted in the identification of 215 single-case-design articles that evaluated the efficacy of FCT to reduce challenging behavior for individuals diagnosed with a disability. FCT resulted in a decrease in challenging behavior for 135 participants. The reviewers rated FCT as an evidence-based practice for individuals with autism, intellectual disability, other health impairments, and multiple disabilities based on What Works Clearinghouse standards. Overall, the extant literature indicates FCT consistently results in the reduction of challenging behavior in children with disabilities. Implications for practice and directions for future research are discussed.